CLASSIFICATION OF SENTENCES BASED ON COMMUNICATIVE INTENT ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the four primary types of sentences classified by their purpose of expression: declarative, interrogative, imperative, and exclamatory. It examines each type’s structure, purpose, and examples, showing how each serves a distinct communicative function. Declarative sentences provide information or statements, interrogative sentences pose questions, imperative sentences give commands or requests, and exclamatory sentences convey strong emotions. The article also highlights the practical application of each sentence type across various contexts, emphasizing how mastering these can enhance clarity, engagement, and emotional impact in communication. The conclusions underscore the importance of understanding and using sentence types effectively to improve personal, academic, and professional communication.